Advantages of Using Extremophilic Bacteria for the Biosynthesis of Metallic Nanoparticles and Its Potential for Rare Earth Element Recovery - Atalah, Joaquín; Espina, Giannina; Blamey, Lotsé; Muñoz-Ibacache, Sebastián A.; Blamey, Jenny M. (Frontiers in Microbiology, 2022)
The exceptional potential for application that metallic nanoparticles have shown, has steadily increased their demand in many different scientific and technological areas, including the biomedical and pharmaceutical industry, bioremediation, chemical synthesis, among others. To face the current challenge for transitioning towards more sustainable and ecological production methods, bacterial biosynthesis of metallic nanoparticles, specially from extremophilic microorganisms, emerges as a suitable alternative with intrinsic added benefits like improved stability and biocompatibility. Currently, biogenic nanoparticles of different relevant metals have been successfully achieved using different bacterial strains. However, information about biogenic nanoparticles from rare earth elements is very scarce, in spite of their great importance and potential. This mini review discusses the current understanding of metallic nanoparticle biosynthesis by extremophilic bacteria, highlighting the relevance of searching for bacterial species that are able to biosynthesize rare earth element nanoparticles.